Monitoring and Handing of 89Sr Injection Site Extravasation in a Patient With Breast Cancer. (July 2020) - Tang, Jiali; Fu, Xiaolin; Hu, Yishu; Zhang, Yiyuan; Shao, Fuqiang
Abstract : Abstract: Extravasation of various imaging tracers during administration was not a rare complication during nuclear medicine practice. However, the occurrence of extravasation of therapeutic radiopharmaceutical was rarely reported. Here we reported a 60-year-old woman with breast cancer and diffuse painful bone metastases who received strontium chloride ( 89 SrCl2 ) therapy to palliate her bone pain. Accidental subcutaneous extravasation in the injection site occurred. The extravasated 89 Sr was absorbed rapidly by arm elevation, squeezing a stress ball, local warming, and gently massaging. Follow-up results showed the patient's bone pain significantly relieved and her right arm remained normal.